HILPDA is a lipotoxic marker in adipocytes that mediates the autocrine negative feedback regulation of triglyceride hydrolysis by fatty acids and alleviates cellular lipotoxic stress - Lei Deng; Shuangcheng Alivia Wu; Ling Qi; Sander Kersten (Elsevier, 2023)
Background: Lipolysis is a key metabolic pathway in adipocytes that renders stored triglycerides available for use by other cells and tissues. Non-esterified fatty acids (NEFAs) are known to exert feedback inhibition on adipocyte lipolysis, but the underlying mechanisms have only partly been elucidated. An essential enzyme in adipocyte lipolysis is ATGL. Here, we examined the role of the ATGL inhibitor HILPDA in the negative feedback regulation of adipocyte lipolysis by fatty acids. Methods: We exposed wild-type, HILPDA-deficient and HILPDA-overexpressing adipocytes and mice to various treatments. HILPDA and ATGL protein levels were determined by Western blot. ER stress was assessed by measuring the expression of marker genes and proteins. Lipolysis was studied in vitro and in vivo by measuring NEFA and glycerol levels. Results: We show that HILPDA mediates a fatty acid-induced autocrine feedback loop in which elevated intra- or extracellular fatty acids levels upregulate HILPDA by activation of the ER stress response and the fatty acid receptor 4 (FFAR4). The increased HILPDA levels in turn downregulate ATGL protein levels to suppress intracellular lipolysis, thereby maintaining lipid homeostasis. The deficiency of HILPDA under conditions of excessive fatty acid load disrupts this chain of events, leading to elevated lipotoxic stress in adipocytes. Conclusion: Our data indicate that HILPDA is a lipotoxic marker in adipocytes that mediates a negative feedback regulation of lipolysis by fatty acids via ATGL and alleviates cellular lipotoxic stress.